Peran Kepemimpinan Kepala Sekolah Dalam Inovasi Manajemen Perpustakaan Untuk Meningkatkan Mutu Pembelajaran Di SMPN 2 Dompu - Basith, Abdul; Saleh, Muhammad; Masniadi, Rudi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to describe the Principal's Leadership Role on Library Management Innovation in improving the quality of learning at SMPN 2 Dompu. To describe Innovations in Procurement Planning, Procurement of Collections, Classification of Collections, Services, Monitoring and Evaluation of the Implementation of the Library Program. This study uses a qualitative research approach, with several data collection techniques in the form of interviews, observations and documentation studies. The subjects of this study were the principal, two library managers, five teachers, five students, and one librarian. The subject of the school only took one school as the respondent, namely SMPN 2 Dompu. This is because SMPN 2 Dompu is a model school set by the West Nusa Tenggara Education Quality Assurance Institute. It is also inseparable from the role of libraries. For this reason, the authors took SMPN 2 Dompu as research subjects. The results of the study are 1). That the principal's leadership in improving the quality of education is very important in improving the quality of education which is assessed as a superior who is the central element determining the direction of school success. The role of the principal at SMPN 2 Dompu has been optimal, so that the principal has more time in school, such as controlling teacher educators every morning, then evaluating, and conducting training on the teacher council so that the school administration is adequate. democratic nature in leading its members. 2). From the results of interviews and observations on the management of the library management at SMPN 2 Dompu, it shows that in planning, compiling, classifying, serving, controlling and evaluating innovation